If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23(x + 4) = 23 Reorder the terms: 23(4 + x) = 23 (4 * 23 + x * 23) = 23 (92 + 23x) = 23 Solving 92 + 23x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-92' to each side of the equation. 92 + -92 + 23x = 23 + -92 Combine like terms: 92 + -92 = 0 0 + 23x = 23 + -92 23x = 23 + -92 Combine like terms: 23 + -92 = -69 23x = -69 Divide each side by '23'. x = -3 Simplifying x = -3
| 3(j+4)=2j+j | | 2*2=2 | | j(j)-16=0 | | 4(a+3)+2=3a+16 | | -28-4y=28 | | [c-7]+14=8 | | 259=-u+29 | | 1.25e+.5=2e-.5 | | x+84=171 | | 12x-4x-15x= | | 7x+8=8x-4 | | 7x-(-56)=28 | | 5k^2-3k+1=6 | | 23b+9=4+66 | | 7(-3x+5)=77 | | 3x^2-36x+27=0 | | 3.50x+50= | | -4x+y=-21 | | 40v(v)-46v-5=0 | | 6x+8x+5+15+3x= | | 56+y=96 | | 11-5x=4-5x | | -3[-2x+5]=-18 | | (x-3)*(3-x)=0 | | 8+9x+8+9x= | | 12x^4y^2-18x^3y^3+24x^2y^2= | | 628806=66.99 | | 85+14=23+y | | 4(2x-1)-6(3-x)=-8 | | 17x-34=17 | | 15x+21y=22 | | .5f-2=1.67f |